Use of MTP kit (Mifepristone and Misoprostol combination pack) for 1st trimester MTP (up to 63 days) at GMERS Dharpur, Patan, Gujarat, India - Jani, Parul S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: MTP has been legalized in India since 1971. MTP pill (Medical abortion) refers for early pregnancy termination (usually before 9 week gestation) performed without any primary surgical interventions. This study was called out to measure its effectiveness and safety as an abortificiant drug. Methods: This is a prospective study of 57 cases, conducted at OBSTETRIC and GYNECOLOGY Department, GMERS Medical College, Dharpur, Patan (N.G.) from April 2017 to April 2018. Results: In present study,61.4% women are of 20-30 years of age. Majority of women are (82.5%) of 2nd and 3rd para. Complete abortion was found in 91.2%. Incomplete abortion was in 7%. And there was no effect in 1.8%. Major side effects were bleeding (84.2%), abdominal pain (85.9%). Misoprostol related side effects are minimal. Conclusions: The present observational study demonstrates that mifepristone and misoprostol combined therapy is an effective and well tolerated medication in Indian adult women (≥18 years) requiring medical termination of intrauterine pregnancy (MTP) up to 63 days’ gestation.